2006
DOI: 10.1097/01.mpa.0000191649.47667.06
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and Oxaliplatin in Patients With Pancreatic Adenocarcinoma

Abstract: The combination of GEM and OXA was well tolerated and showed a promising activity in patients with advanced pancreatic adenocarcinoma; no sequence-dependent pharmacokinetic interaction occurred when comparing the GEM-OXA versus the OXA-GEM sequence, with a 24-hour interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…Encouraging results were obtained in some phase II trials using different schedules with an overall TTP from 3.6 to 5.7 and an OS from 5.6 to 9.5 months (37)(38)(39)(40)(41)(42)(43)(44)47). In particular, a preliminary trial assessed the combination of gemcitabine (1000 mg/m 2 as a 10 mg/m 2 /min infusion on day 1) plus oxaliplatin (100 mg/m 2 as a 2-h infusion on day 2 every two Table II.…”
Section: Gemcitabine and Capecitabinementioning
confidence: 99%
“…Encouraging results were obtained in some phase II trials using different schedules with an overall TTP from 3.6 to 5.7 and an OS from 5.6 to 9.5 months (37)(38)(39)(40)(41)(42)(43)(44)47). In particular, a preliminary trial assessed the combination of gemcitabine (1000 mg/m 2 as a 10 mg/m 2 /min infusion on day 1) plus oxaliplatin (100 mg/m 2 as a 2-h infusion on day 2 every two Table II.…”
Section: Gemcitabine and Capecitabinementioning
confidence: 99%
“…It has also shown promising efficacy for the treatment of other solid tumors and hematological malignancies (5)(6)(7)(8)(9)(10)(11)(12) suggesting more widespread use in the future. In addition to its use as a monotherapy, gemcitabine is often most effective when used as part of a combination therapy, frequently with platinum-based and topoisomerase-targeted chemotherapeutic agents (13)(14)(15).…”
mentioning
confidence: 99%
“…So far, all the published data on the possible PK interaction between gemcitabine and oxaliplatin were incomplete because of the absence of any internal control for the gemcitabine monotherapy in the same patients [9,12,13,16]. This study was designed to directly assess the effect of oxaliplatin on gemcitabine PKs in patients with advanced solid tumors by comparing PK parameters of gemcitabine between the combination day (day 8) and the monotherapy day (day 1).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the different mechanisms of action of the two drugs, the in-vitro evidence of synergy when combined [8] and the broad spectrum of antineoplastic activity with nonoverlapping toxicity, phase I-II studies of the combination have already been conducted in various tumor types [9][10][11][12][13][14][15][16][17]. In a dose-escalation study, we have previously reported that tolerability was excellent and full doses of both drugs, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation